Watch And Play: Engaging Students in Mathematics Learning Through The Alef Education Platform - Afdalianna Abdullah; Akbar Nasrum (PT. Integrasi Sains Edukasi, 2025)
This study aims to examine the effectiveness of the Alef Education platform in improving students' mathematics learning outcomes and their responses to its use at MTs Negeri 1 Kolaka. Alef Education is a digital learning platform that offers instructional videos, educational games, and assessments based on Higher Order Thinking Skills (HOTS). The research employed a post-test only control group design involving two classes: one as the experimental group using Alef, and the other as the control group receiving conventional instruction. Data collection instruments included a mathematics achievement test, student response questionnaires, and interview guides. Quantitative data were analyzed using a t-test, while qualitative data were analyzed descriptively. The results showed that the average learning outcomes of the experimental group were significantly higher than those of the control group (p < 0.05). Students responded positively to the platform, especially appreciating its video lessons and interactive games, which enhanced their conceptual understanding. In-depth interviews also revealed increased student motivation and learning autonomy. These findings suggest that Alef Education is an effective tool for mathematics instruction and holds promise for broader implementation in madrasah as part of digital education strategies.